Design and Build a Web-Based E-Lapor Application as a Citizen's Service Media - Syarif Hidayatulloh; Gema Wahyu Ramadhan (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Rukun Warga 06 Jatisari Bekasi City is a government agency that has direct contact in serving residents. One of the services provided is the submission of complaints in the surrounding environment and the preparation of cover letters for various purposes. The service system provided can be said to be still conventional, and manually documented. With the current system, of course, it is still quite inconvenient for residents, especially when submitting complaints to the surrounding environment because it is not well documented so that follow-up is still not optimal. besides that, there are also problems that occur if residents want to submit a cover letter. The application of information system technology for citizen services will greatly help to make the system even better. Therefore we need an application that can be accessed anytime and anywhere to create a more optimal service. E-Lapor is a web-based application that is intended to help maximize citizen services. The application is designed using UML and built with HTML & PHP programming languages, as well as for interface design using CSS and for the database it is MySQL. Testing this application using black box and usability testing with results showing that the application is functioning properly, in accordance with the design that has been made.